(untitled) (Zoological Records and Reviews, 2025)
The translation of ecological research into effective wildlife conservation planning remains one of the central challenges of applied conservation science, with a well-documented gap between the production of ecological knowledge and its uptake in management decisions. This review examines the mechanisms, barriers, and enabling conditions for knowledge-to-action translation in wildlife conservation planning across Central Europe (Switzerland, Austria, and Germany), synthesising evidence from 164 documented conservation planning processes (2005-2024), structured surveys of 284 conservation practitioners and 196 academic ecologists, and a systematic analysis of 78 species action plans against the quality of their ecological knowledge base. Conservation planning processes that incorporated ecological research through structured decision-making frameworks (SDM; including problem structuring, evidence synthesis, transparent uncertainty quantification, and stakeholder deliberation) showed significantly better implementation rates (68.4% vs. 34.8% of planned actions implemented within 5 years; OR = 3.94, 95% CI: 2.28-6.82) and better biodiversity outcomes (inside-outside biodiversity ratio 1.48 +- 0.18 vs. 1.12 +- 0.14) than those using informal knowledge integration. Practitioner surveys identified the three primary barriers to research uptake as: scientific uncertainty framing deterring decision-makers (cited by 64.8%); temporal mismatch between research timescales and policy cycles (58.4%); and absence of co-production mechanisms between scientists and planners (52.4%). High-quality species action plans – those citing primary research literature, incorporating population viability analysis, and including explicit SMART monitoring targets – showed 2.8-fold higher probability of achieving measurable population recovery within 10 years than low-quality plans. These findings inform evidence-based practice standards for wildlife conservation planning under EU Habitats Directive Article 17 reporting and Kunming-Montreal GBF monitoring frameworks.